Self-reported data - Bartolomé Gutiérrez, Raquel (The crime data handbook, 2024)
One of the central concerns of criminology is how to measure crime. Precise measurement is a precondition for generating valid and reliable knowledge about crime. One of the main methodologies used to measure criminal behaviour is self-reported delinquency (SRD) studies. Although its use is extensive, it is necessary to know its advantages and limitations. In this chapter, we present a brief historical overview of its use in criminology and discuss some aspects that we consider especially relevant. First, we address the question of what information is obtained with SRD surveys about crime. Second, we review the accuracy of the self-report method for knowing the involvement in crime by offenders. Third, we summarize the research on more applied issues, such as forms of administration and the ethical behaviour of researchers who use SRD surveys. Finally, we emphasize the great impact of self-reported data in criminology.